Synthesis and characterisation of TiO based catalyst for the production of FAME from the esterfication of PFAD / Muhammad Imran Sulaiman - Sulaiman, Muhammad Imran (2017)
TiO based catalyst mixed oxides solid catalysts were prepared and evaluated in the esterification of palm fatty acid distillate (PFAD) to produce fatty acid methyl ester (FAME). Esterification was conducted in a batch reactor at 100-170OC temperature ranges. The catalysts were characterized by several techniques such as BET and FTIR. The effect of catalyst preparation condition (catalyst ratio) and the influence of reaction conditions (methanol/PFAD ratio, temperature) were studied. The prepared catalyst with formula TiCr (calcined at 500OC for 2h) gave the maximum FAME conversion at best reaction conditions (160OC, 2h, 4:1 methanol/PFAD molar ratio, 1.5 wt% catalyst dosage). Thus, TiCr has shown promising potentials as heterogeneous catalyst for FAME synthesis from high acid value oils.